Editorial: About the Family - Anna Błasiak (Jesuit University Ignatianum in Krakow, 2019)
A new volume of "Horizons of Education" is devoted to broadly understood family issues. Reflection on the family, which is the fundamental environment of human life, has been undertaken for ages. Today it is a buoyantly developing area of science that arouses a growing interest among researchers, especially in the field of social sciences and humanities....